Mengurangi Animo Pekerja Imigran - Rosyid, Moh. (MUWAZAH, 2017)
This research discusses on the issue of reducing Indonesian migrant workers by cultivating local and natural sources. Data were collected from interview and participative observation. This is a case study based on qualitative approach. In Kudus, some Indonesian migrant workers faced problems in the countries where they worked. In some cases families are lost contact with the workers, some workers were sent back home dying or in critical health condition while some other are sent back home in a coffin. Those who came back healthy faced other problems such as adultery, divorce, or father raped his daughters. There are also who came back in a good health and wealth. Discussing this matter, the government together with the society need to identify and cultivate local sources to help and empower those immigrant workers to find and establish their economic sources in their home town.